Property rights, collective action, and agribusiness - Johnson, Nancy L.; Berdegué, Julio A. (International Food Policy Research Institute, 2004)
The authors state that governments and research and development organizations are increasingly interested in understanding and promoting rural agroenterprises as a way to combat rural poverty. They look at the implications of market orientation for small-scale agricultural producers and the implications of integration for small farms and firms. They conclude that agroindustrialization, which is changing agriculture and rural communities in developing countries, forces farmers and entrepreneurs to change the way they do business. Collective action and networking, a better understanding of how to develop and support those networks, and less traditional forms of organization, such as agricultural cooperatives, is necessary for the development of an efficient and equitable agribusiness sector. -- from Text